KEMAMPUAN ANTAGONIS Trichoderma sp. TERHADAP BEBERAPA JAMUR PATOGEN IN VITRO - Alfizar Alfizar; Marlina Marlina; Fitri Susanti (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
Pathogens often cause disease in plants, causing losses both in quality and quantity, and frequently can cause death on plants cultivated. Biological control begin to be selected in control of pathogens. Antagonist agent Trichoderma is known to control fungal pathogens causing plant diseases. This study looked over inhibition effects of Trichoderma sp. against pathogenic fungi; C. capsici, Fusarium sp. and S. rolfsii. This research was conducted at Laboratory of Plant Pathology Faculty of Agriculture, Syiah Kuala University from April to August 2012. The study began with isolation of the pathogen obtained from chili and soybean crops infected in the field.. Pathogenic fungi isolated were Colletotrichum capsici, Fusarium sp. and Sclerotium rolfsii. Variables observed were wide and diameter colony of Trichoderma sp., diameter colony of pathogens, and the percentage of inhibition. The results showed that Trichoderma sp., had ability to inhibit the growth of pathogen Colletotrichum capsici, Fusarium sp. and Sclerotium rolfsii in vitro. The highest percentage of inhibition of Trichoderma sp. was 68,2% against Colletotrichum capsici, followed by 53,9% against Fusarium sp., and the lowest inhibition was against Sclerotium rolfsii (35.5%).